Production cross sections of 52Mn in alpha-particle-induced reactions on natural vanadium. (June 2022) - Gantumur, Damdinsuren; Aikawa, Masayuki; Khishigjargal, Tegshjargal; Norov, Erdene; Ebata, Shuichiro; Haba, Hiromitsu
Abstract: Activation cross sections of alpha-particle-induced reactions on natural vanadium were measured. The production cross sections of 54, 52g Mn, 51 Cr, 48 V, and 47, 46g Sc were determined up to 50 MeV. The stacked-foil activation technique and high-resolution gamma-ray spectrometry were used. The experimental results were compared with previous experimental data and theoretical calculations in the TENDL-2019 library. The physical yield of the medical radionuclide 52g Mn was derived from the measured cross sections. Highlights: The excitation functions of alpha-particle-induced reactions on nat V up to 50 MeV were measured. The production cross sections of 54, 52g Mn, 51 Cr, 48 V, and 47, 46g Sc were determined. The results were compared with the previous experimental data and the TENDL data. The physical yield of the medical radionuclide 52g Mn was derived from the measured cross sections.